2020
DOI: 10.3390/diagnostics10090699
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Mineral Density and Coronary Artery Calcification in Patients with Osteopenia and Osteoporosis

Abstract: The aim of this study was to investigate the association between bone mineral density (BMD) and coronary artery calcification (CAC) in adults with osteopenia or osteoporosis. A retrospective medical review study was conducted in a regional hospital in southern Taiwan. Medical records of patients who underwent both a coronary computed tomography scan and a BMD measurement were identified. Multinomial logistic regression analyses were used to assess the association between BMD and CAC levels in patients with ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Our results are in line with previous studies which demonstrated a close relationship between osteoporosis and coronary atherosclerotic plaque 25 , 26 . A retrospective study of 246 Taiwan patients has noted that CAC is associated with osteoporosis 25 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with previous studies which demonstrated a close relationship between osteoporosis and coronary atherosclerotic plaque 25 , 26 . A retrospective study of 246 Taiwan patients has noted that CAC is associated with osteoporosis 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous studies which demonstrated a close relationship between osteoporosis and coronary atherosclerotic plaque 25 , 26 . A retrospective study of 246 Taiwan patients has noted that CAC is associated with osteoporosis 25 . The Copenhagen General Population study has shown an inverse relation between BMD and CAC in both men and postmenopausal women 26 .…”
Section: Discussionsupporting
confidence: 93%
“…33 , 34 In a cross-sectional study, a significantly negative association was found between CACs and BMD of lumbar spine, but not total hip. 35 However, another study reported that a significant association of CACs with an increase of osteoporotic fracture and hip fracture risk. 36 These studies implied that the included subjects and BMD sites may be critical when analyzing the association of these two.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous retrospective medical review study on 246 adult patients, no significant independent associations were observed between BMD of the lumbar spine, femoral neck, or total hip with a moderate or high CAC score in patients with osteopenia. In patients with osteoporosis, only the BMD of the lumbar spine was significantly and inversely associated with moderate CAC score [ 22 ]. In addition, we previously reported that TBS was independently associated with moderate but not high CAC scores [ 11 ].…”
Section: Discussionmentioning
confidence: 99%